PENGANTAR MENGENAI TEORI MARXIS TENTANG HUKUM - Wijaya, Endra (Jurnal Dinamika Hukum, 2008)
The opinion of Karl Marx becomes the inspiration for the appearance of the critical philosophy in the field of economics, social, politic and law. The spirit is to criticize the capitalism system that assumed of negative effect for the human life. When those opinion is came into the law, it bring the criticism to attendance of law in capitalist  society. In capitalist society, law is not a free value, it’s not neutral character and always related with the economic factor and also existing politics. Kata Kunci : teori marxis dan sistem kapitalisme